The Rehabilitation Proposal for Seied Golesorkh Street (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
Seied Golesorkh Street is one, the most recent, of the new “cut” streets, at least until 1977, in the historic city of Yazd. The text and images describe the urban redevelopment project of Seied Golesorkh street, an intervention aimed at designing the new road front, but, taking inspiration from the availability of new areas resulting from the demolition, it is committed to provide for new services